THE CORAL REEF CONDITION IN SETAN ISLAND WATERS OF CAROCOK TARUSAN SUB-DISTRICT PESISIR SELATAN REGENCY WEST SUMATERA PROVINCE - Khaidir '; Thamrin '; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis study has been done on the reefs in the coastal waters of Setan Island. Field work was carried out in April 2014 by deploying LIT method. The aim of this study was to find out the condition of the reefs based on the percentage of Hard Living Coral Cover. Three stations as representatives were chosen purposively. The result showed, the type of reefs in the area of study was domitated by fringing reef with different condition on each station. The station 1 showed good condition, it was 58,75%, station 2 showed good condition, it was 54,90% and station 3 showed good condition, it was 54,89%. The coral reefs condition was categorized as good condition.Keywords : Setan Island, Coral reef, Hard Living Coral Cover